2014
DOI: 10.1177/1352458514525870
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy, tolerability and retention rate of azathioprine in 103 aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder patients: a multicentre retrospective observational study from the UK

Abstract: AZA is a modestly effective treatment for NMO. However, many patients discontinue AZA over time and this seems to reflect poor tolerability more than lack of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 41 publications
(61 reference statements)
7
55
2
5
Order By: Relevance
“…While therapeutic interventions with immunosuppressive drugs can reduce the frequency of NMO relapses, 3,[7][8][9][10][11] individual patients in most studies did not respond sufficiently to treatment or experienced major adverse effects. Therefore, better preventive NMO therapies are desirable.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While therapeutic interventions with immunosuppressive drugs can reduce the frequency of NMO relapses, 3,[7][8][9][10][11] individual patients in most studies did not respond sufficiently to treatment or experienced major adverse effects. Therefore, better preventive NMO therapies are desirable.…”
Section: Discussionmentioning
confidence: 96%
“…3 However, relapse prevention remains a challenging issue in NMO because established multiple sclerosis therapies such as interferons, natalizumab, and fingolimod have been reported to show little efficacy or even to be detrimental. [4][5][6] According to smaller case series or retrospective cohort studies, long-term immunosuppression with azathioprine 7 or mycophenolate mofetil 8 is recommended for mild NMO cases, with methotrexate being an alternative treatment option. 3,9 In patients with more severe NMO courses, rituximab 10 and mitoxantrone hydrochoride 11 have been reported to diminish the relapse frequency.…”
mentioning
confidence: 98%
“…Nevertheless, high rates of discontinuation (46%) over time were also reported. 37 Rituximab (RTX). The recommended dose in children is 375 mg/m 2 weekly for 4 weeks, with additional IV infusions depending on the CD191 B-cell count to maintain immunosuppression.…”
Section: Coexisting Autoimmune Diseases and Autoantibodiesmentioning
confidence: 99%
“…AZA was discontinued in 38/ 99 patients, mostly for side effects and lack of efficacy. Another retrospective study of 103 patients with AQP4-IgG-positive NMOSD confirmed these findings, revealed a reduction of the median ARR in 89 % of patients (median of 1.5 pretreatment to 0 on AZA), and an improvement or stabilization of the EDSS in 78 % of patients, but again had a high discontinuation rate of AZA (46 %) [78]. A third retrospective study of 31 patients with AQP4-IgG-positive or AQP4-IgG-negative NMOSD described a reduction in the mean ARR from 2.26 to 0.63 with a failure rate in 53 % of patients, despite concomitant prednisone therapy [79].…”
Section: Azamentioning
confidence: 68%
“…Several studies including a total of almost 400 patients have shown that AZA reduces the ARR, sometimes associated with improvement of neurological disability [17,[74][75][76][77][78][79][80]. A retrospective study evaluating classical NMO and patients with AQP4-IgG-positive NMOSD reported a decrease in the mean ARR from 2.18 to 0.64 in 70 patients treated with AZA for >1 year, with or without concomitant corticosteroid therapy [77].…”
Section: Azamentioning
confidence: 99%